1983
DOI: 10.1111/j.1559-1816.1983.tb02333.x
|View full text |Cite
|
Sign up to set email alerts
|

The Lost Letter Technique Revisited1

Abstract: The present study used the Lost Letter Technique (LLT) to explore the use of personalized letters in assessing community attitudes in a large western metropolitan area. Response to one of the attitude issues was independently validated by subsequent election returns. Results confirm the usefulness of the LLT as a survey tool for sensitive social issues, even with a small sample size, when the envelopes are hand‐addressed and hand‐stamped and drop locations are carefully selected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The continuing success of research using Milgram-style polling techniques (see Bridges et al, 2001 for a recent addition) indicates that people clearly attend to information printed on an envelope when deciding whether or not to mail a lost letter; hence it is fair to assume that participants processed the experimentally manipulated feature and that it simply had no effect on their altruistic behavior. Likewise, it is plausible that the three studies reported here should have sufficed to detect an effect of the experimentally manipulated feature, as a Milgram-style polling study by Simmons and Zumpf (1983) using somewhat smaller sets than those employed here produced results that accurately mirrored subsequent voting patterns on a contested state ballot measure.…”
mentioning
confidence: 71%
“…The continuing success of research using Milgram-style polling techniques (see Bridges et al, 2001 for a recent addition) indicates that people clearly attend to information printed on an envelope when deciding whether or not to mail a lost letter; hence it is fair to assume that participants processed the experimentally manipulated feature and that it simply had no effect on their altruistic behavior. Likewise, it is plausible that the three studies reported here should have sufficed to detect an effect of the experimentally manipulated feature, as a Milgram-style polling study by Simmons and Zumpf (1983) using somewhat smaller sets than those employed here produced results that accurately mirrored subsequent voting patterns on a contested state ballot measure.…”
mentioning
confidence: 71%
“…These in turn had a higher rate of return than those letters addressed to political groups (Jacoby & Aranoff, 1971). Simmons and Zumpf (1983) offered Sears' hypotheses as a reasonable explanation for their higher return rate across conditions (kinds of addressees) for lost letters addressed to individual persons rather than to groups, e.g., committees, and for their high overall rates of return of letters. Sears (1983) explained that the reason why machines and animal characters with human names were evaluated more positively was because the application of names changed their positions on the "personhood" dirnension.…”
mentioning
confidence: 99%
“…In yet another example, Simmons and Zumpf (1983), placed 30 letters for each of seven study conditions and noted that: "The letters were dropped in shopping center stores… or placed under the windshields of cars parked in shopping center lots." (p. 512)…”
Section: Methods In Prior Ll Studiesmentioning
confidence: 99%